Cyber Notary Regulation in Indonesia: Juridical Challenges and Proposed Model for Ensuring the Authenticity and Evidentiary Strength of Electronic Notarial Deeds - Sriyanto, Salsabilla Azahra (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
The rapid advancement of information technology has stimulated significant innovation across legal services, including the notarial field. This study addresses a central research problem: whether the implementation of Cyber Notary in Indonesia can fulfill the legal requirements of authentic deeds under Indonesian positive law. The objective of this research is to examine the juridical challenges of Cyber Notary implementation particularly regarding the authenticity, legality, and evidentiary strength of electronic notarial deeds, while evaluating the regulatory readiness and supporting infrastructure. Using a normative juridical method with a descriptive-analytical approach, this study analyzes statutory provisions, legal doctrine, and comparative practices in jurisdictions such as the United States, Singapore, and Malaysia. The findings reveal that although the Electronic Information and Transactions Law (ITE Law) provides an initial legal foundation, the absence of explicit regulation in the Notary Law (UUJN) and lack of comprehensive technical guidelines impede the legal validity and evidentiary weight of electronic deeds. In addition, challenges arise from identity verification mechanisms, legal certainty standards, and the adequacy of cybersecurity infrastructure. Comparative analysis demonstrates that Indonesia lags behind jurisdictions that have established robust remote notarization frameworks, trusted authentication systems, and integrated digital regulatory mechanisms. Accordingly, this study emphasizes the need for legal reforms through revision of the UUJN, harmonization with the ITE Law, and issuance of detailed implementing regulations supported by secure digital authentication procedures and supervisory structures. This research contributes theoretically by enriching the discourse on modernization of notarial law and practically by offering a regulatory roadmap for developing a legally secure and technologically adaptive Cyber Notary system in Indonesia